PENGARUH FINANCIAL REPORTING QUALITY DAN FRAUDULENT ACCOUNTING TERHADAP INVESTMENT EFFICIENCY DENGAN ASYMMETRY INFORMATION SEBAGAI VARIABEL MODERASI - Silvia Sandra; Sukrisno Agoes (Jurnal Kontemporer Akuntansi, 2025)
The purpose of this research is to obtain empirical evidence about the effects of financial reporting quality and fraudulent accounting on investment efficiency in manufacturing industries listed in Indonesian Stock Exchange during the period of 2018-2020. This research used 88 samples of manufacturing companies that have been previously selected using purposive sampling method. Secondary data was used. This research data was processed using Eviews 12. The result of this research shows that financial reporting quality have a significant and negative effect on investment efficiency whereas fraudulent accounting does not has a significant and negative effect on investment efficiency, while asymmetry information weakness the significant effect of financial reporting quality on investment efficiency and weakness the negative effect of fraudulent accounting on investment efficiency.